2013
DOI: 10.1021/am402310u
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antibacterial Activity of Silver/Polyrhodanine-Composite-Decorated Silica Nanoparticles

Abstract: This work describes the synthesis of silver/polyrhodanine-composite-decorated silica nanoparticles and their antibacterial activity. Polymerization of polyrhodanine proceeded preferentially on the surface of the silica nanoparticles where Ag(+) ions were located. In addition, the embedded Ag(+) ions were reduced to form metallic Ag nanoparticles; consequently, silver/polyrhodanine-composite nanoparticles (approximately 7 nm in diameter) were formed on the surface of the silica nanoparticles. The resulting nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 39 publications
3
68
0
Order By: Relevance
“…52 Recently, in two studies,diffrent design of silica nanoparticles has been found effective in killing bacterial cells without damaging human cells. 53,54 Tank et al found that silica coated silicon nanotubes have excellent antimicrobial activity against both Gram-positive and Gram-negative bacteria. 52 In a separate study, Song et al also showed the antimicrobial effect 10 | J.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…52 Recently, in two studies,diffrent design of silica nanoparticles has been found effective in killing bacterial cells without damaging human cells. 53,54 Tank et al found that silica coated silicon nanotubes have excellent antimicrobial activity against both Gram-positive and Gram-negative bacteria. 52 In a separate study, Song et al also showed the antimicrobial effect 10 | J.…”
Section: Discussionmentioning
confidence: 99%
“…54 Another characteristic feature of silica NP makes them popular is their dispersibility in the aqueous media; a property which most of the nanoparticles lack. 55 There is no doubt that MSPs have great potential in the field of antibacterial nanomedicine, but the bottleneck is insufficient mechanistic studies on how MSP kills bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the studied three metal oxides nanoparticles indeed exhibit much low toxicity, and that their low toxicity can be attributed to their tendency to aggregate in solution which results in limited interaction between the nanoparticles and cell walls of the test organisms (Ching -Ng et al, 2015). Recently, in two studies, different designs of silica nanoparticles have not damage human cells (Liong et al, 2009;Song et al, 2013). Histopathological examination revealed no abnormalities in any tissues (liver, kidney, large intestine, brain, lungs, spleen, heart, stomach and small intestine) after orally exposing silica nanoparticles for 28 days at a daily dose of 2.5 mg. (Mebert et al, 2017).…”
Section: B a D Cmentioning
confidence: 95%
“…So far it has been reported the use of ascorbic acid as a reducing agent for metal NPs synthesis by using microwave irradiation (Qin et al, 2010;Chekin and Ghasemi, 2014). Silver NPs are of interest because of their antibacterial activity and localized surface plasmon resonance properties (Song et al, 2013;Panáček et al, 2006;Amendola et al, 2010; * Corresponding author: bojana.laban@pr.ac.rs Mogensen & Kneipp, 2014). Developing the route of synthesis enabled the control of desired size, shape, and capping agents.…”
Section: Metalmentioning
confidence: 99%